Diffuse subarachnoid hemorrhage following ventriculo-peritoneal shunt insertion for acute obstructive hydrocephalus from large glomus jugulare tumor: case report - Shiferaw, Mestet Yibeltal; Teklemariam, Tsegazeab Laeke; Wondimagegnewu, Eyob Zenebe; Gebrewahd, Dejen Tekiea; Yesuf, Ermias Fikru; Mekuria, Bereket Hailu; Abelti, Sebboona Baisa (Frontiers in Surgery, 2024)
Background Glomus jugulare tumors (GJTs) are rare intra-cranial tumors. Commonly, these lesions present with cranial nerve palsies, headaches, and hydrocephalus. Rarely, GJTs present with spontaneous subarachnoid hemorrhage. However, there has never been a report of diffuse subarachnoid hemorrhage following ventriculoperitoneal shunt insertion in a patient who developed hydrocephalus secondary to any brain tumor in general or glomus jugulare tumors in particular. Observation The authors presented an extremely rare complication of diffuse subarachnoid hemorrhage following the insertion of a ventriculoperitoneal shunt (VPS) in a 61-year-old female patient who was diagnosed to have both clinical and radiologic features of acute obstructive hydrocephalus secondary to a highly vascular huge glomus jugulare tumor. Conclusion Subarachnoid hemorrhage following ventriculoperitoneal shunt insertion for hydrocephalus caused by a mass lesion is an extremely rare complication. Preoperative CT angiography should be strongly considered to look for the associated vascular malformations in extremely vascularized mass lesions. Given the not ubiquitous availability of all therapeutic options for GJTs, especially in low and middle income settings contributes for the poor outcome of GJTs and it fosters a global neurosurgery agenda.